Cell Entry of Lymphocytic Choriomeningitis Virus Is Restricted In Myotubes - Iwasaki, Masaharu (2014)
In mice persistently infected since birth with the prototypic arenavirus lymphocytic choriomeningitis viurs, viral antigen and RNA are readily detected in most organs and cell types but remarkably absent in skeletal muscle. Here we report that mouse C2C12 myoblasts that are readily infected by LCMV, become highly refractory to LCMV infection upon their differentiation into myotubes. Myotube’s resistance to LCMV was not due to an intracellular restriction of virus replication but rather an impaired cell entry mediated by the LCMV surface glycoprotein. Our findings provide an explanation for the observation that in LCMV carrier mice myotubes, which are constantly exposed to blood-containing virus, remain free of viral antigen and RNA despite myotubes express high levels of the LCMV receptor alpha dystroglycan and do not pose an intracellular blockade to LCMV multiplication.